Pediatric Traumatic Brain Injury and Autism: Elucidating Shared Mechanisms - Rahul Singh; Ryan C. Turner; Linda Nguyen; Kartik Motwani; Michelle Swatek; Brandon P. Lucke-Wold (Behavioural Neurology)
Pediatric traumatic brain injury (TBI) and autism spectrum disorder (ASD) are two serious conditions that affect youth. Recent data, both preclinical and clinical, show that pediatric TBI and ASD share not only similar symptoms but also some of the same biologic mechanisms that cause these symptoms. Prominent symptoms for both disorders include gastrointestinal problems, learning difficulties, seizures, and sensory processing disruption. In this review, we highlight some of these shared mechanisms in order to discuss potential treatment options that might be applied for each condition. We discuss potential therapeutic and pharmacologic options as well as potential novel drug targets. Furthermore, we highlight advances in understanding of brain circuitry that is being propelled by improved imaging modalities. Going forward, advanced imaging will help in diagnosis and treatment planning strategies for pediatric patients. Lessons from each field can be applied to design better and more rigorous trials that can be used to improve guidelines for pediatric patients suffering from TBI or ASD.